Hematological Profiles Due to Mask Use at Maximum Physical Activity - Pahala Tua Hutajulu; Wahida Y. Mapandin; Budi Kristanto; Yohanis Manfred Mandosir; Syahruddin Syahruddin (UNIVERSITAS NEGERI MAKASSAR, 2022)
The Application of 5M; Washing hands, Keeping a distance, Using masks, Avoiding crowds, and Reducing mobility are powerful weapons to prevent and break the chain of transmission of Covid 19 which until now is still mutating. Masks are recommended to always be worn when outside the home and when carrying out daily activities. Many people continue to wear masks when doing sports. The purpose of this study was to determine the hematological profile due to the use of masks at maximum physical activity. This study is a quasi-experimental study using a single group pretest-posttest design. The variables studied were the amount of hemoglobin, the number of hematocrits, the number of erythrocytes, and the number of leukocytes between before and after performing maximum physical activity. Data analysis was carried out by paired t-tests. The results showed that there was a significant difference in the amount of hemoglobin before and after maximum physical activity (p<0.05), there was a significant difference in the number of hematocrits before and after maximum physical activity (p <0.05), there was a significant difference in the number of erythrocytes before and after maximum physical activity (p<0.05), there was a significant difference in the number of leukocytes before and after maximum physical activity (p<0.05).